Mastering your fellowship - Klaus von Pressentin; Mergan Naidoo; Andrew Ross; Richard Cooke (South African Family Practice)
The series, “Mastering your Fellowship”, provides examples of the question format encountered in the written examination, Part A of the FCFP(SA) examination. The series aims to help Family Medicine registrars prepare for this examination. Model answers are available online.